The sultan's tigers - Lacey, Josh (Houghton Mifflin Harcourt, 2013)
Tom, who comes from a long line of criminals, travels with his roguish uncle to India to find a family treasure--an antique jewel-encrusted tiger stolen from the sultan's throne hundreds of years ago.